Role and mechanism of IGFBP5 in the real-ambient particulate matter exposure-induced chronic lung injury - Chen, Ningning; Qi, Yuan; Ma, Wanli; Zhu, Xiaoxiao; Li, Xiaoying (Frontiers in Pharmacology, 2025)
BackgroundInflammation and oxidative stress are the main pathological processes of particulate matter (PM)-induced lung injury. Insulin-like growth factor binding protein 5 (IGFBP5) is an important secretory protein related to inflammation and oxidative damage in several tissues, whereas its roles in PM-induced lung adverse effects remain largely unexplored.MethodsIn the present study, mice were housed in an individual ventilated cage (IVC)-based real-ambient PM exposure system for eight weeks. Transcriptomics was employed to analyze gene expression alterations.ResultsIGFBP5 was significantly downregulated after PM exposure. Functional investigations demonstrated that IGFBP5 downregulation exacerbated PM-induced oxidative damage, as evidenced by elevated levels of reactive oxygen species (ROS) and malondialdehyde, as well as decreased levels of superoxide dismutase 2 (SOD2). Conversely, IGFBP5 overexpression effectively rescued these oxidative stress phenotypes. Mechanistically, IGFBP5 downregulation attenuated extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation, thereby impairing SOD2 catalytic activity and amplifying ROS accumulation. Co-treatment with si-IGFBP5 and ERK1/2 signaling pathway inhibitor PD98059 could further aggravate the production of ROS in cells. Moreover, microRNAs (miRNAs) are an important class of gene expression regulators. We found that the upregulated hsa-miR-33a-5p repressed IGFBP5 translation by forming a silencing complex with Argonaute protein 2 (AGO2) in a real-ambient PM exposure system, which further led to the suppression of the ERK1/2-SOD2 signaling pathway and increased levels of ROS.ConclusionThis study revealed that the downregulation of IGFBP5 promoted oxidative damage in lung cells by inhibiting the IGFBP5-ERK1/2-SOD2 pathway, and targeted inhibition of hsa-miR-33a could alleviate PM-induced lung injury by upregulating IGFBP5.